A bridge from will to authenticity: The role of meaning - Eksi, Halil; Sahin, Yahya; Koca, Dilek Akca; Eminoglu, Zehra; Eksi, Fusun (Springer, 2023)
Examining the mediating role of meaning in the effect of will on authenticity in adults is the purpose of this study. The sample is a total number of 289 adults. The correlation between will, authenticity and meaning was examined in SPSS 22. A positive relationship was found between will and personal meaning, between will and pure authenticity, between personal meaning and pure authenticity. The model was tested using AMOS to examine role of meaning in the effect of will on authenticity. It has been seen that the meaning in the effect of the will on authenticity has a mediating role.
Keywords: Will; Free will; Volition; Authenticity; Personal meaning